1973
DOI: 10.2118/4346-pa
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Stream Tube Methods To Predict Waterflood Performance of an Isolated Inverted Five-Spot at Favorable Mobility Ratios

Abstract: Failure of Stream Tube Methods To Predict Waterflood Performance of an Isolated Inverted Five-Spot at Performance of an Isolated Inverted Five-Spot at Favorable Mobility Ratios Introduction Since their introduction by Higgins and Leighton in 1962, stream-tube methods (STM) have been used by a number of authors to make approximate waterflood and gas flood calculations. The principal justification for the methods is given by Higgins and Leighton, who present ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Previous theoretical work and field experiments have demonstrated that the relationship between injected fluid and production is not always simple [14,15]. The basic merit of streamline simulations is that well productivity can be explained as the flux of fluid carried through the streamtubes outlined by discrete bundles of streamlines into the well (Morel-Seytoux 1965 [16][17][18][19][20][21]).…”
Section: Reservoir and Well Designmentioning
confidence: 99%
“…Previous theoretical work and field experiments have demonstrated that the relationship between injected fluid and production is not always simple [14,15]. The basic merit of streamline simulations is that well productivity can be explained as the flux of fluid carried through the streamtubes outlined by discrete bundles of streamlines into the well (Morel-Seytoux 1965 [16][17][18][19][20][21]).…”
Section: Reservoir and Well Designmentioning
confidence: 99%
“…This approach recognizes the different nature of these physical processes and the potential advantage of using different numerical approaches for simulation. Similar approaches and ideas presented in this paper, but not considered to be streamline methods, are described by Bratvedt 7,8 , Hales 30 , Ewing 21 , Glimm 27 and others 24,40,43,44 . The basic streamline approach also is described by King 50,51 and others 9,13,18,52,54 .…”
Section: Introductionmentioning
confidence: 75%
“…Early applications for hydrocarbon reservoir simulation were reported by Fay and Pratts 22 in the 1950's, Higgins et al [32][33][34] in the early 1960's, and Pitts and Crawford 53 , LeBlanc and Caudle 41 and Martin and Wegner et al 43,44 in the 1970's.…”
Section: Introductionmentioning
confidence: 99%
“…The answer centers on the attempt t o capture the nonlinearities that exist in multiphase flow. Only three authors Martin et al [85], Martin and Wegner [84], Renard [lo71 address the idea of updating the streamtubes rather than using total flow resistance. Mathematically, updating the streamtubes is an appealing approach because local flow velocities are updated, and the original definition of a streamtube as carrying a volumetric rate equal to the difference in the value of its bounding streamlines is maintained.…”
Section: Reasons For the Riemann Approachmentioning
confidence: 99%